2006
DOI: 10.3354/ame044263
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the heterotrophic dinoflagellate Pfiesteria piscicida in Korean waters and its consumption of mixotrophic dinoflagellates, raphidophytes and fish blood cells

Abstract: -1). Calculated grazing coefficients on co-occurring Amphidinium spp., H. akashiwo, and cryptophytes were up to 1.07, 0.45, and 0.22 h -1 , respectively. Our results suggest that grazing by P. piscicida potentially has a considerable effect on algal populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 38 publications
(50 reference statements)
4
51
0
1
Order By: Relevance
“…1). This is similar to the results for P. piscicida (Jeong et al 2006). The growth rate of the dinoflagellate, Gymnodinium sp.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…1). This is similar to the results for P. piscicida (Jeong et al 2006). The growth rate of the dinoflagellate, Gymnodinium sp.…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed that thecate dinoflagellates are not available as for prey PLD species (Table 1). A similar result was also reported by Jeong et al (2006); P. piscicida is able to feed on unarmored phytoflagellates, including Heterosigma akashiwo, whereas they did not feed on thecate mixotrophic dinoflagellates, with the exception of Heterocapsa rotundata (Lohmann) Hansen. In Jeong et al (2006), P. piscicida efficiently utilized the thecate dinoflagellate H. rotundata.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Lewitus et al 2002). Their cell length and width are approximately 5 to 25 μm and 3 to 20 μm, respectively, and the ranges of the cell lengths and widths overlap between species (Jeong et al 2006). Further, their shapes are very similar, whereas their plate patterns and DNA sequences clearly differ (Steidinger et al 1996, Jeong et al 2005b ABSTRACT: To investigate interactions between the heterotrophic dinoflagellates Pfiesteria piscicida, Stoeckeria algicida, and Luciella masanensis and their protozoan and metazoan predators, we measured the growth and/or ingestion rates of the heterotrophic dinoflagellate Oxyrrhis marina, the ciliate Strombidinopsis jeokjo, and the calanoid copepods Acartia spp.…”
Section: Introductionmentioning
confidence: 95%